Field theory actions for ambitwistor string and superstring - Berkovits, Nathan [UNESP]; Lize, Matheus [UNESP] (Springer, 2018)
We analyze the free ambitwistor string field theory action for the bosonic string, heterotic string and both GSO sectors of the Type II string. The spectrum contains non-unitary states and provides an interesting consistency test for one-loop ambitwistor string computations.
Keywords: BRST Quantization; String Field Theory; Superstrings and Heterotic Strings